Pembiayaan Berbasis Kekayaan Intelektual Akibat Wanprestasi oleh Para Pelaku Usaha Ekonomi Kreatif - Manggala, Ferdiansyah Putra; Dewi, Vinka Kurnia (Universitas Batanghari Jambi, 2024)
The objects of debt collateral are generally objects that have a exists for (tangible asset) such as land, buildings, vehicles and so on. However, in Law concerning the Creative Economy, precisely in Article 16, it is explained that the government facilitates intellectual property-based financing schemes that have economic value for creative economy business actors which will be further regulated in a government regulation. In terms of supporting the use of intellectual property as collateral objects to obtain credit, the government issued Government Regulation no. 24 of 2019 concerning Implementing Regulations of Law concerning the Creative Economy. So that creative economy actors in this case can take advantage of these facilities to develop their potential. Based on this background, the author formulates two problem formulations, namely: how are intellectual property rights (IPR) regulated for creative economy businesses as objects of debt collateral? What are the resolution efforts if a dispute occurs due to default by creative economy business actors? This thesis research uses normative juridical methods with a statutory approach (statue approach) and conceptual approaches. The legal materials used are primary legal materials and secondary legal materials using the library study method of collecting legal materials with research analysis using deductive methods.